The Application of Power Point in Teaching Writing Within the Genre-Based Approach - Soraya, Kety (JEDLISH : Journal Of Education and English Language Teaching, 2023)
This study aims at investigating the application of PowerPoint in teaching writing within the Genre-Based Approach to the ninth-grade students in one of junior high schools. The prime focuses of this study are to find out how PowerPoint is used in teaching writing within the Genre-Based Approach and what students’ perceptions are. In order to answer the questions, the study employed descriptive qualitative research. The instruments used to obtain the data were observation, questionnaire, and interview. The findings subsequently reveal that PowerPoint could help teacher to have better performance in explaining writing materials by incorporating it with Genre-Based Approach in which some features of PowerPoint have made easy for teacher to implement Genre-Based Approach in teaching writing. It also reveals that the vast majority of the students have showed positive responses due to the advantages of PowerPoint found, such as getting better understanding, clarity and interest. Accordingly, PowerPoint is still worth using in classrooms as a teaching media.